THE ASPECT OF SOCIOCULTURAL OF ENGLISH NOBLEMAN IN THE 18TH CENTURY AS SEEN ON THE FILM ENTITLED â€œTHE DUTCHESSâ€ BY SAUL DIBB (A SOCIOLOGICAL APPROACH) - Ch. Evy Tri Widyahening, Yonas Mustika Adi (UNIVERSITAS SLAMET RIYADI, 2014)
The objective of this research is to describe the aspect of sociocultural of English nobleman in the 18th century as seen on the film entitled â€œThe Duchessâ€ by Saul Dibb and the approach that is used is Sociological Approach. This study focuses on the cultural component in English nobleman's life in the 18th century as reflected in the film. The aspects of sociocultural in English nobleman's life in the 18th century are good. The development of culture grows fast and the concept of life in their life is changing, from traditional concept to modern concept. They hold firmly their principle as nobleman, as holding trust concept, education, and norm of the things in local of nobility of British is very strong. At 18th century, it is also showed that the position of countess is still being placed lower in any aspects of life. The concept of thinking of British nobleman at 18th century is highly developed and the education is heavily affected by French. The Aspects of sociocultural of English nobleman have affected also the public of British in general. Â Keywords : The aspect of sociocultural, English nobleman, The Duchess film Â